Principals’ leadership skills to meet the national strategy for education in basic schools - Ajmi, Hadi Rashed Al (Journal of Education and e-Learning Research, 2024)
The objective of this study is to investigate the principals' leadership skills in elementary schools to meet the national educational strategy outcomes based on the teachers' views. A quantitative- descriptive approach was applied. The questionnaire was used to collect data. The validity of the questionnaire was measured and the reliability results using Cronbach alpha were 0.948 for educational leadership skills and 0.859 for educational outcomes. The questionnaire was distributed in both male and female schools. A random sample of 385 teachers was included. The collected data were analyzed using descriptive statistics and structural equation modeling to measure the effects of different variables. The findings indicated that the teachers in the sample had five to fifteen years of experience. The teachers showed principals in the elementary schools have moderate educational leadership (3.39). The results showed that the highest trait that existed among the principals was crisis management with a high-weight regression coefficient (0.693), visionary leadership (0.653) and ethical leadership (0.601). The effect of adaptability, communication skills and strategic planning was less. The least common traits among the principals of elementary schools were emotional intelligence and decision-making skills. The research suggested establishing a programme for elementary school principals to develop their leadership skills in order to support the achievement of national educational objectives.